Entry Through the Narrow Door: The Costs of Just Failing High Stakes Exams - Steve Machin; Sandra McNally; Jenifer Ruiz-Valenzuela (Center for Economic Studies and ifo Institute (CESifo), 2018)
In many countries, important thresholds in examinations act as a gateway to higher levels of education and/or good employment prospects. This paper examines the consequences of just failing a key high stakes national examination in English taken at the end of compulsory schooling in England. It uses unique administrative data to show that students of the same ability have significantly different educational trajectories depending on whether or not they just pass or fail this exam. Three years later, students who just fail to achieve the required threshold have a lower probability of entering an upper-secondary high-level academic or vocational track and of starting tertiary education. Those who fail to pass the threshold are also more likely to drop out of education by age 18, without some form of employment. The moderately high effects of just passing or failing to pass the threshold in this high stakes exam are therefore a source of educational inequality with high potential long-term consequences for those affected.
Keywords: I20; I21; I24; 330; high stakes examinations; manipulation; English